Tathbiiq al-Qiyam al-Bunyawiyyat Fii Ta'liim al-Mahaaraat al-Lughawiyyat al-Arba' - Ahmad Zubaidi (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
The concept of "structuralism" can be said to be from the word "structure", which means constant and organized links between groups of phenomena. As for "structuralism", people are often understood by the movement of thought or the method of science that affects ideology. Another definition of constructivism is the way of thinking that views all that exists as “all” made up of connected, interrelated structures. And the values ​​of this ideology can be deduced from their application in the field of teaching the four language skills, as the fact that each skill is taught cannot be separated from the other. And teaching the skill of listening, for example, has a strong association with other skills. The relationship between a language skill and other skills can be said to be the concept of "parts in a whole